The Void of Quantum Reality - Dolenc, Sašo (Filozofski vestnik, 2013)
Zeilinger’s fundamental principle of quantum physics is presented and discussed in connection to the metaphysical implications of quantum theory. Similarities between problems of irrational proportions within the Pythagorean vision of the universe and problems instigated by the interpretation of quantum physics in our everyday vision of reality are investigated.